Presence of Sugarcane yellow leaf virus (SCYLV) in sugarcane (Saccharum spp.) isolated from Colima - Barbosa Villa, Maria Ines; Cruz Jaramillo, José Luis; Silva Rojas, Hilda Victoria; García Mariscal, Karina de la Paz; García Preciado, José Concepción; Guzmán, Manuel de Jesús Bermúdez (Revista Mexicana de Ciencias Agrícolas, 2018)
Sugarcane is one of the important industrial crops worldwide and is affected by various viral diseases, including the Sugarcane yellow leaf virus (SCYLV). In Mexico, this virus has been detected based on symptomatology and °Brix; however, the diagnosis based on these parameters is not conclusive. The objective of the study was to detect the presence and distribution of SCYLV in sugarcane areas of western Mexico (Colima, Jalisco and Nayarit) and to determine the phylogenetic origin of a Colima isolate. The work was developed in the Tecoman Experimental Field during 2013-2014. Total RNA was isolated from collected leaves and RT-PCR was performed with oligonucleotides specific for SCYLV. A total of 233 samples were analyzed and the incidence of SCYLV carrier plants was 14.6%, affecting the hybrids CP 72-2086, Mex 69-290 and Atemex 96-40. The BLAST analysis showed that the partial CP sequence of Colmex-317 (512 bp) is homologous with sequences from Brazil, China, India, Kenya and USA and also shares identity percentages higher than 99% with other sequences from several countries. The phylogenetic analysis of Colmex-317 with partial sequences and complete genomes of SCYLV isolated from different parts of the world revealed that the Mexican isolate belongs to the Brazilian genotype (BRA) and was grouped with sequences from Brazil, China, Kenya and South Africa. However, it is necessary to evaluate a larger number of isolates and longer sequences to determine if the BRA genotype is the only one present in Mexico.